1983
DOI: 10.1002/1097-0142(19830201)51:3<534::aid-cncr2820510328>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The coin lesion of the lung: A review of 955 resected coin lesions

Abstract: The retrospective study of 955 coin lesions of the lung showed 49% to be malignant. The proportion of malignant lesions increased with age. In patients older than 60 years of age, 65% of the lesions were malignant; in this group, bronchogenic carcinoma was the most frequent lesion. The delay prior to resection was especially pronounced in both younger patients and in patients with smaller lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
10

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(43 citation statements)
references
References 17 publications
2
31
0
10
Order By: Relevance
“…Multiple studies examining the correlation between age and malignancy have found that that the risk for malignancy within an SPN is approximately double for patients over the age of 50 compared with patients younger than the age of 50 (6). Unfortunately, it is difficult to identify an age below which primary pulmonary malignancy need not be considered within the differential diagnosis of SPNs discovered at chest radiography.…”
Section: Patient Agementioning
confidence: 99%
“…Multiple studies examining the correlation between age and malignancy have found that that the risk for malignancy within an SPN is approximately double for patients over the age of 50 compared with patients younger than the age of 50 (6). Unfortunately, it is difficult to identify an age below which primary pulmonary malignancy need not be considered within the differential diagnosis of SPNs discovered at chest radiography.…”
Section: Patient Agementioning
confidence: 99%
“…La explicación para esta gran variabilidad de resultados esta dada por diversidad de los grupos etarios estudiados -poblaciones de mayor edad tienen mayor riesgo de tener lesiones malignas-y la metodología empleada en su detección (radiografía, TC) 6 …”
Section: Diagnóstico Diferencialunclassified
“…Cáncer Pulmonar: Aunque todas las variantes histológicas se pueden presentar inicialmente como un NPS, este tipo de presentación ocurre principalmente en los Adenocarcinomas, con una incidencia del 8-38% de todos los NPS, y un 30-50% de las lesiones malignas, y en los Carcinomas de células escamosas, que representan un 2-30% de todos los NPS y entre un 10-37% de las lesiones malignas 6,21,23,24 . Los carcinomas de células pequeñas y los carcinoides en menor grado también se pueden presentar como un NPS 25,26 .…”
Section: Lesiones Malignasunclassified
See 2 more Smart Citations